COVID-19 as a female members of parliament label: gendered perspectives on the post-2020 election intraparty conflict in Tanzania - Edwin Babeiya (Cogent Social Sciences)
This study examined public opinion regarding a case involving 19 female Special Seats Members of Parliament (also called COVID-19), who belong to Chama cha Demokrasia na Maendeleo (CHADEMA), Tanzania’s major opposition party. The study’s main objective was to identify the forms of public opinions on the matter to establish whether such opinions converged or diverged from the institutionalised negative public orientation towards the role of women in Tanzanian politics. The study collected data from Tanzania’s popular social media platform Jamiiforums1 through a systematic review of 23 conversations (threads) initiated by the forum’s registered members for the public to discuss this saga. The results showed that despite a lack of public consensus over the ‘COVID-19’ designation, there were four main public perspectives on the case. These included women being seen as rebels, traitors, political instruments and victims of gender stereotypes. The four themes generated from the findings reflected, to a great extent, the Tanzanian society’s ingrained negative perception towards women’s role in politics. This study recommends, among other considerations, the party’s adoption of legal and structural reforms that grant more decision-making powers to women, particularly on matters that concern them, such as the nomination of special seat candidates.